P163 Transmural healing assessed using MRI scores is associated with better outcomes and is a potential therapeutic target in patients with Crohn's disease. (25th January 2019) - Buisson, A; Vignette, J; Allimant, C; Reymond, M; Pereira, B; Bommelaer, G; Hordonneau, C
Abstract: Background: The poor acceptability of repeated colonoscopies limits the use of endoscopic mucosal healing as therapeutic target in patients with Crohn's disease (CD). MRI is better accepted than endoscopy, is able to perform a concomitant assessment of ileocolonic inflammation and to detect CD complications. We aimed to evaluate whether transmural healing assessed using MRI scores was associated with decreased risk of surgery, hospitalisation and therapeutic intensification in patients with CD. Methods: From a database including all the consecutive patients who performed an MRI to assess luminal CD between January 2012 and June 2018 in our IBD unit, we selected all the patients with CD (> 18 years-old) who underwent two MRI with: (1) objective signs of inflammation on the 1st MRI, (2) the second MRI indicated to assess therapeutic efficacy, (3) follow-up > 6 months and no surgery between the two MRI. All the patients underwent MRI assessing the small bowel and the colon using a standardised protocol (no bowel cleansing the day before and no colonic distension). Complete transmural healing was defined as normalisation of MRI. Partial transmural healing was defined as a decrease of at least 25% of Clermont score or MaRIA in each active segment. Results were expressed as Hazard Ratio (HR) and 95% confidence interval [95% CI]. Results: Overall, 443 patients undergoing 889 MRI were screened for the study. Among them 274 patients were included (mean age 33.1 ± 15.8 years, median CD duration 7.0 [2.0–13.0] years, 36.4% smokers, 31.4% prior intestinal resection, L1 = 51.5%, L2 = 5.5% and L3 = 43.1%, 25.9% perianal lesions, 35.4% stricturing CD and 31.0% fistulizing CD). At the time of the second MRI, the patients received one or several medications among: steroids (6.3%), immunosuppressants (45.2%), anti-TNF agents (65.7%) or ustekinumab (2.6%). The median interval between the 2 IRM was 9.2 months [6.0–14.1]. Overall, 53 patients had a CD-related bowel resection, 72 patients (26.3%) required CD-related hospitalisation and 163 patients (59.5%) needed therapeutic intensification (median follow-up = 14.9 mois [4.3–31.4]). In multi-variate analysis (Cox model), complete or partial transmural healing was associated with reduced risk of surgery (HR = 0.13 [0.05–0.38] ; p < 0.001), of subsequent hospitalisation (HR = 0.25 [0.11–0.56]; p = 0.001) and therapeutic intensification (HR = 0.08 [0.03–0.20]; p < 0.001). Complete transmural healing showed a lower risk of therapeutic intensification compared with partial transmural healing ( p < 0.05). Conclusions: Transmural healing assessed using MRI scores is associated with favourable outcomes in patients with CD and should be used as therapeutic target both in daily practice and clinical trials.